O DEUS ROSIANO: ANÁLISE TEOLÓGICO-LITERÁRIA DAS IMAGENS AMBÍ-GUAS DE DEUS EM GRANDE SERTÃO: VEREDAS - Alonso Júnior, Hugo Fonseca (2010)
Everything is and is not . This dissertation aims at analyzing some ambiguous images of God in the novel Grande Sertão: Veredas [The Devil to Pay in the Backlands]. Therefore, this analysis is an interdisciplinary attempt of reading and interpretation, where Theology and Literature are in dialogue. From the novel by João Guimarães Rosa, in the light of the literary hermeneutics critique and of theological reflection, we searched on pointing out that Guimarães Rosa s writings present God in an ambiguous way. This affirmation is possible as it is noticed in the human temporariness, poeticized by the author and personified by Riobaldo, the sine qua non trace of the way of seeing worlds mixed . When remembering and retelling stories of his life, Riobaldo opens space to the Mystery: - Nonada . In each crossing, the protagonist-narrator reflects about God through poetic speech whose diverse images suggest a very upset God . With no use of final theological and/or philosophical frameworks, Rosa provokes us when shows that the God who runs everything shows up and manages to escape in the backlands-universe, a physical-mythical place. It is in the backlands that we try to follow God s traces according to Riobaldo s iris. It is a look of constant movement between the dark and the revealed, between what is and what is not.(AU)